2017
DOI: 10.1152/ajpcell.00350.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of posttranslational modifications of engineered cysteines on the substituted cysteine accessibility method: evidence for glutathionylation

Abstract: The substituted cysteine accessibility method (SCAM) is widely used to study the structure and function of channels, receptors and transporters. In its usual application, a cysteine residue is introduced into a protein which lacks native cysteines following which the accessibility of the residue to the aqueous compartment is assessed. Implicit, and generally assumed, is that if the cysteine-substituted residue is not available to react with sulfhydryl reagents it is not exposed to the extracellular compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In this construct, serine was substituted for Cys66 and Cys298 and an HA (hemagglutinin) tag was added to the C-terminus. This template eliminates the disulfide bond and reaction with a sulfhydryl-reacting reagent should the procedure require pretreatment with dithiothreitol to remove a modifying molecule that interferes with biotinylation and function (13,14). This results in only a negligible decrease in function (13,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this construct, serine was substituted for Cys66 and Cys298 and an HA (hemagglutinin) tag was added to the C-terminus. This template eliminates the disulfide bond and reaction with a sulfhydryl-reacting reagent should the procedure require pretreatment with dithiothreitol to remove a modifying molecule that interferes with biotinylation and function (13,14). This results in only a negligible decrease in function (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…The topology of the transporter has been defined as well as residues that play a role in proton-coupling, proton binding, the affinity of the carrier for its folate substrates and the rate of oscillation of the carrier among its conformational states (4,713). Recently, transmembrane helices were identified that participate in the formation of a gate at the external interface of the aqueous pathway (14).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The topology of this transporter has been defined and is typical of the solute carrier (SLC) superfamily of transporters with 12 transmembrane helices, 6 on either side of a large internal loop, with N-and C-termini located within the cytoplasm. [7][8][9][10] The exofacial regions at the membrane-aqueous interface of transmembrane helices 1, 2, 7, and 11 were recently shown to come together to form a gate at the extracellular entrance to the aqueous translocation pathway, 11 as has been reported for other solute transporters. 12,13 The proximity of residues in these helices was established by crosslinkages between cysteine-substituted residues within this region of the gate.…”
Section: Introductionmentioning
confidence: 80%
“…18,19 Analysis of PCFT protein expression at the cell surface Cell surface expression was determined by biotinylation of accessible PCFT lysine residues with EZ-Link sulfo-NHS-LC, as has been previously described in detail. 10,11 Briefly, washed cells were treated with 1 mg/mL of EZ-Link sulfo-NHS-LC for 30 min at room temperature (RT). All subsequent steps were at 4°C.…”
Section: Influx Measurementsmentioning
confidence: 99%
See 1 more Smart Citation